Spatiotemporal dynamics during the transition to thermoacoustic instability: Effect of varying turbulence intensities. (December 2018) - George, Nitin B; Unni, Vishnu R; Raghunathan, Manikandan; Sujith, RI
An experimental study on a turbulent, swirl-stabilized backward facing step combustor is conducted to understand the spatiotemporal dynamics during the transition from combustion noise to thermoacoustic instability. By using a turbulence generator, we investigate the change in the spatiotemporal dynamics during this transition for added turbulence intensities. High-speed CH* images of the flame (representative of the field of local heat release rate fluctuations (q · ' ( x, y, t ))) and simultaneous unsteady pressure fluctuations (p ' ( t )) are acquired for different equivalence ratios. In the study, without the turbulence generator, as the equivalence ratio is reduced from near stoichiometric values, we observe an emergence of coherence in the spatial dynamics during the occurrence of intermittency, enroute to thermoacoustic instability. As the turbulence intensity is increased using the turbulence generator, we find that there is an advanced onset of thermoacoustic instability. Spatial statistics and the instantaneous fields ofp ' ( t ) q · ' ( x, y, t ) show that during the transition from combustion noise to thermoacoustic instability, the emergence of coherent spatial structures in the instantaneous fields ofp ' ( t ) q · ' ( x, y, t ) for the experiments with higher turbulence intensities is advanced. However, as the equivalence ratio is reduced further, we notice that higher turbulence intensities result in the reduction of the strength of the pressure oscillations during the state of thermoacoustic instability. We find that, at these low equivalence ratios, there is a decrease in the coherence due to the dispersal ofp ' ( t ) q · ' ( x, y, t ), which explains the reduction in the strength of the pressure oscillations.